Tentorial Notch Meningiomas: Innovative Preoperative Management and Literature Review - Cannizzaro, Delia; Milani, Davide; Zaed, Ismail; Tropeano, Maria Pia; Nicolosi, Federico; Costa, Francesco; Servadei, Franco; Fornari, Maurizio; D'Angelo, Vincenzo; Cardia, Andrea (Frontiers in Surgery, 2022)
Background: Tentorial meningiomas account for only 3-6 % of all intracranial meningiomas. Among them, tentorial incisura (notch) location must be considered as a subgroup with specific surgical anatomy and indications, morbidity, and mortality. In this study, we propose an update on preoperative management in order to reduce postoperative deficits. Methods: We retrospectively collected adult patients treated for incisural meningioma between January 1992 and December 2016 in two different neurosurgical departments. Demographic, clinical and neuroradiological preoperative and postoperative data were analyzed. In the most recent subgroup of tumors a pre-operative digital simulation was performed to define a volumetric digital quantification of the tumor resection. A review of the pertinent literature has been also done. Results: We included 26 patients. Median age was 58,4 years. Onset neurological signs were: cranial nerve deficit in 9 patients, hemiparesis in 7, gait disturbance in 3 and intracranial hypertension in 3 patients. Simpson grade I removal was achieved in 12 patients, II in 10, III in 3, IV in 1 patient. An overall rate of 23% post-operative complications were observed. The average follow-up duration was 68.5 months. Residual tumor was reported in 8 patients. Five underwent gamma knife radiosurgery. In 34.6% of patients, the surgical approach was chosen with preoperative digital planning estimating the potential volume of postoperative residual tumor, the target for radiosurgical treatment. Conclusions: A multidisciplinary approach to plan incisural meningiomas management is important. To lower postoperative morbidity and mortality a careful preoperative case analysis is useful. A planned residual tumor, supported by preoperative simulation imaging, could be safely treated with radiosurgery.